The Figure of the Victim in the Fairy Tales with the T 651 Motif of the Devil as a Farm-hand - Piotrowski, Robert Piotr (Literatura Ludowa. Journal of Folklore and Popular Culture, 2020)
The article argued for the thesis that, in the fairy tales with the theme T 651 "The Devil as a Farm-hand", there is an agreement between the otherworld, represented by the devil, and the host human. Simultaneously, the motif of stealing bread is actually a veiled motif of sacrifice for a demonic world of archaic provenance. The author analyses selected narratives with the T 651 theme although stealing bread, that is the victim, and the service is present in practically all of its realizations.